ANALISIS TINGKAT KESADARAN HUKUM BERLALU LINTAS SEBAGAI PILAR KESELAMATAN DI JALAN RAYA (STUDI KASUS DI POLRES SUKOHARJO) - Febriyanti, Ainnur; Suyahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the level of legal awareness among road users and the factors contributing to traffic violations in Sukoharjo Regency. Legal awareness is examined through four indicators proposed by Soerjono Soekanto, namely legal knowledge, legal understanding, legal attitude, and legal behavior. This research employs a qualitative approach using interviews, observations, and documentation, supported by an interactive data analysis model by Miles and Huberman. The findings show that although road users possess adequate knowledge and understanding of traffic regulations, such awareness is not fully reflected in their actual driving behavior. Violations remain prevalent, particularly not wearing helmets, running red lights, failing to use license plates, and using modified exhausts. These violations are influenced by low self-awareness, environmental and social factors, limited supervision, and insufficient enforcement facilities such as ETLE. Efforts to address these issues—such as education, socialization, law enforcement, infrastructure improvement, and routine police monitoring—have been implemented but have not yet produced optimal results. The study concludes that increasing legal awareness requires a comprehensive strategy combining consistent education, strengthened enforcement, and the development of a culture of traffic discipline.